2009
DOI: 10.1097/mej.0b013e328320ad2f
|View full text |Cite
|
Sign up to set email alerts
|

Adult epiglottitis: 6 years experience in a university teaching hospital in Hong Kong

Abstract: Adult epiglottitis is a relatively rare but potentially lethal disease. It seems to be increasing in incidence in other countries. The objective of this study was to examine the common presentations and clinical course of adult epiglottitis in Hong Kong. Retrospective review of 80 consecutive cases of adult epiglottitis admitted between 2000 and 2005. A rising trend in the incidence of adult epiglottitis was observed. The mean age (SD) was 49 years (15.7) and the male-to-female ratio was 2.5:1. Disease present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
33
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 14 publications
3
33
0
Order By: Relevance
“…Previous studies have demonstrated that 8% to 39% of patients with supraglottitis require airway management [1][2][3]6,[14][15][16][17][18]. In our study, the physicians secured the airways of 26% of the patients in the ED; and no further airway managements were required during hospitalization.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Previous studies have demonstrated that 8% to 39% of patients with supraglottitis require airway management [1][2][3]6,[14][15][16][17][18]. In our study, the physicians secured the airways of 26% of the patients in the ED; and no further airway managements were required during hospitalization.…”
Section: Discussionmentioning
confidence: 72%
“…The strategy for airway management for adult supraglottitis patients remains controversial because there are no reliable predictors of sudden airway obstruction in these patients [4,[14][15][16][17][18]. Previous studies have demonstrated that 8% to 39% of patients with supraglottitis require airway management [1][2][3]6,[14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…It may prove to be a rapid, noninvasive, and effective diagnostic tool for identifying and measuring the epiglottis 2 . Although the incidence of acute epiglottitis is very rare, the disease can be progressive and life threatening; therefore, early and safe diagnosis is required 1 , 2 , 5 . Conventional radiography cannot usually be performed on critically unstable patients in the intensive care unit or even in the ED.…”
Section: Discussionmentioning
confidence: 99%
“…Epiglottic abscess occurs almost exclusively among adults, and management of epiglottitis with abscess can be more complicated than epiglottitis alone, although studies report conflicting data regarding mortality. According to a seminal case review in 1977, mortality in patients with epiglottic abscess can be as high as 30%, although some more recent series report no fatalities [6][7][8]. Although the literature varies considerably in the estimation of its incidence and outcomes, epiglottic abscess is a potentially life-threatening condition that requires prompt diagnosis and appropriate treatment.…”
mentioning
confidence: 99%
“…The treatment for both epiglottitis and epiglottic abscess involves airway management and antibiotics, but the presence of abscess may complicate airway management. Reported treatment modalities include artificial airway [8], incision and drainage [15][16][17], and spinal needle aspiration [7], in addition to medical therapy and observation (ie, conservative therapy or watchful waiting). Clinical decision making regarding interventional vs conservative therapy is multifactorial and should consider the degree of obstruction and likelihood of developing life-threatening airway compromise; the patient's medical status and comorbidities; and, if conservative therapy is considered, the ability of caregivers to detect and respond to sudden-onset respiratory distress.…”
mentioning
confidence: 99%